Understanding gap between perception and expectations for artificial intelligence: Implications for sustainable development goals 4 and 9 - Skenderi, Besnik; Zejnullahu, Safet; Skenderi, Diamanta; Selimi, Ferid (Edelweiss Applied Science and Technology, 2024)
This research is focused on the gap created in the perception and expectations of Kosovar students in the implementation of artificial intelligence during their learning and education. The research was conducted with students who had attended training on Artificial Intelligence that to identify the gap between their perception and expectations regarding artificial intelligence. The aim of this study is to investigate the understanding gap between perceptions and expectations of artificial intelligence and to provide answers to the research questions posed in this paper. Obejectiv of the study is to shed light on the need for Sustainable Development Goal 4, Quality Education, by emphasizing the importance of inclusive and equitable AI literacy, and also for Development Goal 9, Industry, Innovation, and Infrastructure, by fostering innovation and supporting the development of resilient and sustainable AI infrastructure. During the research we used purposive sampling since we already had access to the database showing which students had attended the training and were certified for artificial intelligence by Microsoft. Bazed on the use of adaptive learning technology, wich is one of the ways Artificial Intelligence can have an impact on student psychology, and based on each student’s performance, interests and learning style, we concluded this technology tailors the learning experience to them, and learning is more effective and efficient, and motivation and engagement also increase more.